2018
DOI: 10.1002/hed.25416
|View full text |Cite
|
Sign up to set email alerts
|

Utility of first positron emission tomography‐computed tomography scan as a prognostic tool following treatment of sinonasal and skull base malignancies

Abstract: Background The prognostic value of the first posttreatment whole body integrated positron emission tomography‐computed tomography (PET/CT) scanning in patients with sinonasal/skull base malignancies is undetermined. Methods We retrospectively reviewed the data of all patients that underwent surgery for sinonasal/skull base malignancies in 2000‐2015. The results of the pretreatment and posttreatment PET/CT findings and the clinical course were retrieved. Results Thirty‐eight patients (average age 60.6 years, 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 29 publications
(94 reference statements)
2
7
0
Order By: Relevance
“…PET/CT has also been used as a prognostic tool. A retrospective study described that an absence of pathologic FDG uptake at the first posttreatment PET/CT was associated with better OS 39 …”
Section: Sinonasal Squamous Cell Carcinomamentioning
confidence: 99%
“…PET/CT has also been used as a prognostic tool. A retrospective study described that an absence of pathologic FDG uptake at the first posttreatment PET/CT was associated with better OS 39 …”
Section: Sinonasal Squamous Cell Carcinomamentioning
confidence: 99%
“…FDG-PET/CT has also been suggested for serving as a prognosticator in patients with sinonasal malignancies [ 58 , 59 ]. Absence of pathologic uptake at the first post-treatment PET/CT is highly predictive of significantly better OS, as for other SCCs of the HN [ 60 ].…”
Section: Pre-treatment Assessmentmentioning
confidence: 99%
“…First, there is a lack of standardized SUV cutoff value suggesting whether a sinonasal lesion is malignant. 36,39 Many studies also showed the inability of PET scans to distinguish postsurgical inflammation from disease recurrence, 50,56 highlighting the…”
Section: Discussionmentioning
confidence: 99%
“…A total of 7 studies were found discussing the role of PET scan for prognosis in sinonasal malignancies. 27,[34][35][36][37][38][39] A summary of each study, their level of evidence, and an assessment of risk of bias can be found in Table 4. All 7 studies were retrospective and had a serious risk of bias.…”
Section: Sinonasal Carcinomasmentioning
confidence: 99%